Can a Case be made for the Provision of Government Funded Social Assistance to Refugees in South Africa? Defining a Constitutional Standard for Refugee Protection in South Africa - Machingambi, Nyaradzo (Department of Public Law, 2014)
This paper is a critique of the implementation of the progressive refugee protection through the local integration policy that has been established by the South African Government. It is premised on the belief that the South African government has failed to create an 'enabling environment for refugees' and that this failure makes it imperative for the South Africa government to remove the exclusion of refugees from their social security scheme. The case put forward by this paper is that the inclusion of refugees into the South African social security scheme will not only improve the quality of its refugee protection policies but it will make them more compatible with constitutional standards.